MOTIVATIONS, IMPORTANCE, CHALLENGES AND PERSPECTIVES OF SOCIAL CONTROL IN HEALTH - Carlos Junglos; Felipa Rafaela Amadigi; Rosani Ramos Machado; Jacks Sorato (Universidade Federal do Paraná, 2019)
Purpose: To understand the motivations, importance, challenges and perspectives for acting as local health counselors in the Unified Health System.Method: A qualitative and descriptive study of the exploratory type conducted with 15 local health counselors, from a southern Brazilian capital, from January to March 2017, through semi-structured interviews based on the Collective Subject Discourse method. Results: The motivations were linked to the possibility of social contribution to the community; the importance of identifying the local health council as a collective and supervisory space; the challenges (poor attendance at meetings and influence of party politics; perspectives) focused on the need for greater participation, community interest and more efficient health management.Conclusion: Knowledge, awareness and empowerment are fundamental to increase the performance and participation for a better exercise of social control in health.